Influence of multi-species biofilm formed in vitro from different environmental samples on the drug-resistance traits of resident bacteria - Munshi, Saurab Kishore; Haque, Tamanna; Noor, Rashed (Bangladesh Journal of Microbiology, 2019)
Present study was designed to investigate whether the formation of multi-species biofilm impart any effect on the enhancement of the antibiotic resistance of the planktonic cells residing in the general nutrient enriched environments. In this regard, surface water of pond, mud from agricultural field, pharmaceutical waste waters, municipal waste water, hospital waste water and the domestic waste samples were collected and were induced to form an in vitro multi-species biofilm. All samples were found to contain huge array of pathogenic bacteria. The pathogenic isolates both from the bulk samples and their corresponding biofilms were subjected to antibiogram assay using 13 commonly used antibiotics. An extended frequency of drug resistance was observed in case of biofilm isolates. The findings of present study revealed that a number of bacterial isolates which showed sensitivity towards antibiotics, acquired drug-resistance when they were isolated from biofilms. Bangladesh J Microbiol, Volume 35 Number 2 December 2018, pp 108-114